Mortgaging the Skies? Legal Status of Apartment Ownership in South Sumatra’s Financial Practices - Sakti, Bima Bayu Putra; Ramli, Asmarani (Universitas Negeri Semarang, 2024)
The development of vertical housing needs such as flats in big cities, including in the South Sumatra Province, encourages the importance of legal certainty over ownership and utilization of flat units in the national financing system. The Certificate of Ownership Rights for Flat Units (SHM Sarusun) is recognized as a property right that can be used as an object of debt collateral by being burdened with Mortgage Rights. This provision is regulated in Law Number 20 of 2011 concerning Flats and Law Number 4 of 1996 concerning Mortgage Rights (UUHT), and is an implementation of Article 51 of the Basic Agrarian Law (UUPA). Article 27 of the UUHT explicitly states that the imposition of collateral rights on flats and ownership rights on flat units is possible and legally valid. This study highlights the implementation of these provisions in South Sumatra, emphasizing how banks in this region utilize SHM Sarusun as credit collateral in the form of Flat Ownership Credit (KPRS). In practice, financial institutions consider aspects of ease of binding, certainty of value, ease of execution, as well as supervision and maintenance of collateral objects. Therefore, flats built on shared land, with legal individual ownership rights, have become an effective collateral alternative in the financing system in South Sumatra. This study shows that SHM Sarusun not only has a social function as a residence, but also has a strong and relevant economic value in supporting legal and guaranteed financing access.